Watermarking digital images for copyright protection - BOLAND, FRANCIS MORGAN (IEE, 1995)
A watermark is all invisible mark placed on an image that can only be detected when the image is compared with the original. This mark is designed to identify both the source of a document as well as its intended recipient. This paper discusses various techniques for embedding such marks in grey scale and colour digital images. It begins specifying the requirements that an effective image watermarking scheme must possess, followed by a review of current and novel techniques based on image transforms
International Conference on Image Processing and its Applications: 5th: Edinburgh: 1995
PUBLISHED
Keywords: Copyright protection; Image processing; Steganography; Spread spectrum communications